The Caffeine Content of Energy Drinks in accordance with the Information on the Package Label - Said Kudema; Claus Thomas; Helena Ngowi (Advances in Public Health)
Six different brands of energy drinks (EDs) were analyzed to determine the concentration of caffeine in accordance with the information on the package label. Approximately 28.1 milligrams per 100 milliliters (mg/100 ml) of caffeine was present in the Mo energy drink brand, which was nearly 1.5 times the caffeine concentration listed on the product label. The energy drink with the highest caffeine content was Dragon, which contained 30.1 mg/100 ml, or a total of 150.5 mg per 500 ml bottle. Manufacturers of energy drinks (EDs) should accurately list the amount of caffeine and other ingredients on the product label so that consumers know how much of each ingredient they are taking. Taking too much caffeine can be bad for your health.